Virtual Reality Simulation Technology for Cardiopulmonary Resuscitation Training: An Innovative Hybrid System With Haptic Feedback. (February 2019) - Almousa, Omamah; Prates, Joana; Yeslam, Noor; Mac Gregor, Dougal; Zhang, Junsong; Phan, Viet; Nielsen, Marc; Smith, Richard; Qayumi, Karim
Objective. Althoughcardiopulmonary resuscitation (CPR) skills are lifesaving skills, the gap between awareness and actual training remains significant. Advances in technology are shaping the future of education and innovative learning solutions are essential to facilitate effective and accessible training. This project objective is to develop a self-directed educational system for hands-onCPR training usingvirtual reality (VR) technology. Methods. HTC VIVE was the chosenVR engine, and Unity3D was the software used for development.CPR skills including chest compressions, rescue breathing, and automated external defibrillator (AED) are taught in VR through focused instructions, demonstrations, and simulated interactive scenarios with hands-on training sessions. A tracking system was designed using virtual planes and VIVE-Tracker for accurate measurements of chest compressions (rate, depth, and recoil), hands' position and AED. A real mannequin was integrated in theVR space and overlaid with virtual 3D-human model for realistichaptic feedback and hands-on training. VIVE-controller was used for precise calibration between the mannequin location in real environment and the virtual human model inVR space. Results. TheVR-CPR prototype was designed to be generic, approachable, and easy to follow. Realism and interaction were achieved through 3D virtual scenes simulating common sites at which cardiac arrest may occur. Variety in scenarios and gamification features like scoring and difficulty levels of training were made to enhance users' engagement. TheVR -mannequinhybrid system enabled quality training and immersive learning experience. Further, real-time feedback and scoring system are built for self-directed learning and optimal performance. Conclusions. The developedVR-hybrid product is a structured educational tool for hands-onCPR training and ongoing practice. This innovative technology provides self-directed learning with no restrictions of time, place, or personnel, which are the main challenges with current traditional courses. This product is a promisingCPR training initiative in the evolution of digital education.